The promotion of local sustainable development through the planning of integrated tourist routes. The case study of Archanes village. - Zouridaki, Maria (2019)
This thesis concerns a holistic assessment of sustainable cultural heritage routes and how and whether it could have a financial, social, environmental and cultural impact on the local development financially, socially, environmentally and culturally. The thesis is divided into seven chapters. The first chapter deals with the introduction, acting as a general reference to the issue under study and examines the aim of the dissertation. The second chapter analyzes the sustainability in the tourism field. Apart from the new challenges in sustainable tourism development and the definitions of the issues, the international and European policies have been also discussed. The third chapter refers to cultural tourism definition, the combination of cultural tourism and local development, as for the implementation of cultural tourism into route tourism. In the fourth chapter, the methodologies of the dissertation have been analyzed. The first one is the Cultural Route Evaluation Model (CREM) and the second one is the methodology for assessing the cultural tourism potential of cultural heritage sites. The fifth chapter is a general commentary of the case study, Archanes village. Demographics, economy, employment and transport are the elements that have been discussed. In the sixth chapter, the results of the three proposed sustainable cultural routes in Archanes village have been analyzed. The first one is the “Minos pathway”, the second one is “From the Byzantine Era to the sovereignty of Venetians in Archanes” and the third one is “The route of German General Kreipe’s Abduction”. Finally, chapter 7 analyzes the findings of our study during this thesis and the future research.